Manajemen Lingkungan Perairan Dalam Mendukung Keberlanjutan Kualitas Air Bersih: Pendekatan Berbasis Ekosistem, Teknologi, Dan Partisipasi Masyarakat - Fakta Perjuangan Lombu; Destriman Laoli; Ratna Dewi Zebua (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Clean water quality is a fundamental component in sustaining aquatic ecosystems and supporting human life. Increasing pressures from pollution, climate change, and weak water resource management systems require integrated and sustainable environmental management strategies. This article aims to examine various aquatic environmental management strategies that support the sustainability of clean water quality through a literature review approach. The study applies a systematic literature review method by analyzing relevant national and international scientific journals focusing on ecosystem-based management, environmental technology innovations, climate change adaptation, as well as regulatory and community participation aspects. The findings indicate that ecosystem-based approaches, such as mangrove conservation and integrated coastal management, play a significant role in maintaining ecological functions and improving water quality. Furthermore, technological innovations including biofilters, membrane systems, and Internet of Things (IoT)-based real-time monitoring significantly enhance the effectiveness of water quality control and monitoring. However, challenges remain in the form of weak institutional coordination and limited community participation, which hinder effective policy implementation. Therefore, a holistic approach integrating ecological, technological, policy, and social dimensions is essential to achieve sustainable clean water management and long-term aquatic ecosystem resilience